Pekanbaru Convention Center Dengan Penekanan Bangunan Futuristik - Syalam Haryadi; Ratna Amanati; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru city developed rapidly, becoming a place of activities that support all aspects of the emerging economies in Riau province. The existence of competition in the market to seize, resulting in the emergence of new discoveries. Competition occurs because the needs of the wider community publications. And so we need a container to hold meetings which aim to produce something that can improve a variety of sectors, whether economic, social, and political, even education and entertainment. Meeting the existing building does not stand alone, but part of the hotel buildings and large office buildings. In addition, buildings associated with the activities of the convention no one has the image of an attractive visual appearance. The problem basically is how the format of the building that can accommodate a variety of conventions, the circulatory system of the building, and application of the concept Futuristic at the convention building. The concept raised for the building of this convention is the development of futuristic elements, namely Dynamic Facades, Technological Innovation and Sustainable. The method used is modeling Futuristic forms using computer software and supported by modeling animation techniques to design a dynamic roof notching, the application of technology in the parking system, the formation of the facade that moves through the role of the sensor to the movement of the sun, and all aspects in accordance with the request Futuristic basic concepts and objectives. Designed so that the Convention Center can accommodate a variety of activities that are conventions with the circulatory system of the building are arranged for the convenience of visitors, and in accordance with the concept of futuristic buildings with elements developed, namely Dynamic Facades, Technological Innovation and Sustainable.Keywords: Convention Center, Futuristic Architecture